Kajian Penggunaan Obat Insomnia sebagai Penyakit Penyerta pada Salah Satu Rumah Sakit Khusus Daerah di Kalimantan Timur - Serly Monika Putri; Laode Rijai; Risna Agustina (Proceeding of Mulawarman Pharmaceuticals Conferences, 2020)
Insomnia is a sleep disorder such as dissatisfaction with sleep quality, difficulty in sleeping and maintaining sleep, causing physical and emotional symptoms that affect performance and also cognitivity. The existence of mental disorders such as depression, fatigue and anxiety which culminate in insomnia so that a person does not sleep soundly. The purpose of this study is to determine the characteristics, variations of the diseases that cause insomnia, drug use, and drug interactions that occur. The research method used an observational retrospective method by tracing medical record data at a special regional hospital in East Kalimantan with a total sampling technique during 2019. The results obtained for characteristic data that insomnia was greater for women (57%) at the age of 56-65 years (40%) with primary and junior high school education (30%) who do not work (77%) and who do not have a history of disease (93%) and insomnia due to anxiety (94%). For the variation of insomnia, based on the causes and history of the disease, whether there is anxiety disorder or anxiety. Treatment is done with 87% single therapy, namely using the drugs Alprazolam (8%), Clozapine (41%), Fluoxetine (4%), Risperidone (8%), Lorazepam (8%), Diazepam (11%), Zolpidem tartrate (4%), Amitripthyline (4%), Clonazepam (4%), and Clorpromazin (8%) while 13% uses 2 combination of drug therapy is using combination of Fluoxetine and Amitripthyline (25%), Clozapine and Sertraline (50%), and Maprotiline hydrochloride and Clobazam (25%). The potential interactions are entirely pharmacokinetic interactions of the metabolic phase with major severity of 75% and moderate severity of 25%.